2022
DOI: 10.1021/acsapm.1c01715
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Healing Composite Material with Microwave Absorbing and Anticorrosion Properties Accelerated by Carboxylated Carbon Nanotubes

Abstract: Due to rapid self-healing characteristics, hydrogen-bonding composite materials have great potential in biological and medical fields. Carbon nanotubes have been widely used in composites and engineering fields because of their high aspect ratio and excellent mechanical, electrical, and chemical stability. Therefore, understanding how to combine carbon nanotubes with a hydrogen bond self-healing interaction can be important to expand the application field of selfhealing materials. In this paper, we designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…20 In another study, CNTs-COOH enhanced PAA/polyvinylpyrrolidone hydrogel showed enhanced mechanical properties and fast self-healing property that it could achieve 75% mechanical self-healing efficiency within 5 min. 21 Herein, dynamic hydrogen bonds and metal coordination were adopted to construct multifunctional PAA/PVA composite hydrogels with a DN network. Al 3+ was introduced into the system to form metal coordination bonds with − COOH of PAA and cCNTs to improve mechanical properties and self-healing ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In another study, CNTs-COOH enhanced PAA/polyvinylpyrrolidone hydrogel showed enhanced mechanical properties and fast self-healing property that it could achieve 75% mechanical self-healing efficiency within 5 min. 21 Herein, dynamic hydrogen bonds and metal coordination were adopted to construct multifunctional PAA/PVA composite hydrogels with a DN network. Al 3+ was introduced into the system to form metal coordination bonds with − COOH of PAA and cCNTs to improve mechanical properties and self-healing ability.…”
Section: Introductionmentioning
confidence: 99%
“…A self-healing chitosan and polyacrylamide hybrid hydrogel with excellent flexibility and puncture resistance was prepared by carboxylated multiwalled CNTs (c-MWCNTs) cross-linked with chitosan . In another study, CNTs-COOH enhanced PAA/polyvinylpyrrolidone hydrogel showed enhanced mechanical properties and fast self-healing property that it could achieve 75% mechanical self-healing efficiency within 5 min …”
Section: Introductionmentioning
confidence: 99%
“…Until now, only a few self-healable materials and designs for absorption-dominant EMI shielding or MWAs have been reported [18][19][20][21][22][23] despite significant advances made in the development of self-healing electrically conductive composites. [24][25][26][27][28][29][30][31] Although self-healing supramolecular materials are very promising, for example, due to their extraordinary stretchability, selfadhesiveness, and self-healing characteristics, [32][33][34][35] the level of properties required for EMWs absorption is not often possible to achieve at 1-30 GHz range with a thickness of less than 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31] Although self-healing supramolecular materials are very promising, for example, due to their extraordinary stretchability, selfadhesiveness, and self-healing characteristics, [32][33][34][35] the level of properties required for EMWs absorption is not often possible to achieve at 1-30 GHz range with a thickness of less than 1 mm. For example, in the case of non-patterned conductive materials, this can be due to initial surface reflection resulting from improper impedance matching at the air interface, [14,21,22] and with resistive gradients introduced to the structure the overall thickness increases. Thus, achieving efficient absorption and attenuation of EMWs with soft polymer composites and their multilayered or multimaterial assemblies often requires also blending of a relatively high content of electric and/or magnetic solid filler particles to the polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials, such as carbon nanotubes , and graphene, , have been considered as good candidates for electromagnetic functional materials due to their lightweight, high stability, and outstanding dielectric properties. However, their impedance mismatch and weak magnetic loss severely limit their application in the field of microwave-absorbing materials .…”
Section: Introductionmentioning
confidence: 99%